Synthesis and characterization of alpha-nickel (II) hydroxide particles on organic-inorganic matrix and its application in a sensitive electrochemical sensor for vitamin D determination - Canevari, Thiago da Cruz [UNESP]; Cincotto, Fernando Henrique [UNESP]; Landers, Richard; Machado, Sergio Antonio Spinola [UNESP] (Elsevier B.V., 2014)
This paper describes the synthesis, characterization and application of amorphous nickel (II) hydroxide particles, alpha-Ni(OH)(2), onto a hybrid material composed of silica and graphene oxide, SiO2/GO. The sol-gel process using HF as the catalyst was used to obtain this organic-inorganic matrix. The Ni(OH)(2) were prepared directly on the surface of the matrix using nickel (II) acetate and N, N-dimethylformamide (DMF) as a solvent. The SiO2/GO/Ni(OH)(2) material was characterized by scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HR-TEM), energy-dispersive X-ray (EDX), X-ray photoelectron spectroscopy (XPS) and electrochemical techniques. A glassy carbon electrode modified with the SiO2/GO/Ni(OH)(2) material was used in the development of a sensitive electrochemical sensor for the determination of vitamin D-3 by pulse differential voltammetry. A well-defined electro-oxidation peak of vitamin D-3 was observed in sodium hydroxide at pH 13. The results indicated that the resultant SiO2/GO/Ni(OH)(2) modified electrode is highly selective and very sensitive with a limit of detection, in pure laboratory solutions of 3.26 x 10(-9) mol dm(-3); therefore, it can be used to detect vitamin D3 in real samples. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Electrochemical sensor; graphene oxide; hybrid materials; nickel hydroxide; Vitamin D